Ecoepidemiologia de Triatoma brasiliensis nos estados da Paraíba e Rio Grande do Norte: indicadores entomológicos e estruturas ecotípica e composicional etária - Lucena Filho, Maurício Lilioso de (2015)
First, this study evaluated the risk imposed by Triatoma triatoma in the Chagasic epidemiology in distinct rural sites in Paraíba (PB; Cajazeiras, São José de Espinharas, Condado, Santa Teresinha and São Mamede) and Rio Grande do Norte (RN; Caicó and Currais Novos) with the use of entomological indicators. The rate of natural infection by T. cruzi and the parasite diversity, according to the two major lineages (TCI e TCII) were also evaluated via molecular techniques. With the field information, the compositional age structure of natural T. brasiliensis populations was also characterized. A total of 3,021 triatomines were captured, with a notable prevalence of T. brasiliensis (80%), followed by T. pseudomaculata (16%) and T. petrochii (4%). Overall, the domestic colonization was low and most of collected insects were peridomestic, which minimizes the risks of T. cruzi transmission. Even though Condado had exhibited the highest indexes of domiciliary infestation (50%) and colonization (40%), these indexes were followed by null natural infection by T. cruzi and low triatomine density (10.1 insects/house). Contrarialy, for Currais Novos there were hight triatomine density (37%) and colonization (37%), as well as natural infection by T. cruzi (mean 24.4%), suggesting it is the most exposed municipality to T. cruzi human infection. The observed variation in natural infection by T. cruzi in domiciliary unities is probably associated to ecotope structures, as in PB municipalities insects are found in chicken crops whereas in Currais Novos (RN) rock, cobblestone and branch piles are infested as much by T. brasiliensis as they are by sylvatic Caviidae mammals (Galea spixx and Kerodon rupestris). The lower (mean 3.4%) natural infection prevalence for T. cruzi in wild natural populations of T. brasiliensis in spots of PB if compared to those sampled in RN (mean 51.8%) is probably associated with environmental degradation of natural habitats observed in the first. Molecular techniques pointed out the two major parasite lineages of T. cruzi co-occurring in peridomiciles and also in sylvatic environments. From September to December it is observed a higher incidence of adults in the sylvatic environments, if compared to field work of March and studies surveyed from literature. It alerts for the possibility of a higher incidence of domiciliary invasions of winged forms of T. brasiliensis during the last months of the year.